VIOLATIONS OF CONVERSATIONAL MAXIMS IN THE MOVIE SHERLOCK HOLMES: THE FINAL PROBLEM - Josep H. Pukoliwutang; Deane Wowor; aloysius Rettob (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
This research aims at finding the type of maxims that violate from all the conversations that happen in this movie and describing how the character violates the maxims in the movie Sherlock Holmes: The Final Problem. The researchers use the qualitative method in this research. The researchers take the data from the movie script and also the movie itself. The researchers analyze the data using qualitative data analysis by Donald Ary. The findings of this research show that violations of maxims do occur in this movie. The characters from this movie violate all types of conversational maxims, overall there are 30 violations of the maxims that occur in this movie. The characters of this movie violate the maxims by flouting, opting in, and opting out the utterances.